Endovascular therapy of symptomatic high-grade stenosis of left internal carotid artery in C6 segment using Elutax “3” Neuro pDEB - Latacz, Paweł; Popiela, Tadeusz; Brzegowy, Paweł; Kwinta, Borys; Chwała, Maciej; Simka, Marian (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Intracranial atherosclerotic disease (ICAD) is a well-known cause of stroke and is responsible for approximately 5–10% of all strokes [1]. The annual risk of recurrent stroke in symptomatic ICAD is around 9–12% despite optimal medical treatment [2]. Patients presenting with symptomatic ICAD have been managed endovascularly (ET) for over two decades. Still, although initial results of such treatment were encouraging, the rates of periprocedural complications and restenoses were high, 15% and 34%, respectively [2].